Pembelajaran Bahasa Makassar Berbasis Transformasi Generatif di Sekolah Dasar - Rivai, Mantasiah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This study aims to describe the implementation of the Generative Transformation Grammar approach in the teaching of the Makassar language in primary school. The steps in conducting this development research are preparation, applying the model, conducting tests, evaluation, and revision. The subjects of this study were students of SDN Pa’bangngiang, Somba Opu Sub-district, Gowa Regency, who were randomly selected. Through the results of the tests, the students’ performance was measured, and the data were collected and analyzed descriptively. The teaching and learning instructional materials developed include lesson plans, a students’ book, and a teacher’s guide based on the TTG approach. The results of the study show that the implementation of the TTG approach in the teaching of the Makassar language effectively increases the students’ knowledge and their performance in using the language.